Rinse Willet, The Geography of Urbanism in Roman Asia Minor - Jackson, Mark P.C. (Journal of Greek Archaeology, 2021)
The contrast between the classical cities of South West Turkey and the inland areas of Asia Minor has long struck visitors to the region. In 1907, Gertrude Bell recorded her visits to several Roman cities in Western Asia Minor including: Ephesus, Priene, Miletus, Halicarnassus, Aphrodisias, Hierapolis and Sagalassos before she journeyed on to the Central Anatolian plateau to work at Binbirkilise, The Thousand and One Churches, on the Karadağ, one of several ancient volcanos dominating the central Anatolian plateau.